Building a place brand from the bottom up: A case study from the United States. (October 2017) - Hudson, Simon; Cárdenas, David; Meng, Fang; Thal, Karen
In an increasingly competitive global marketplace, the need for towns and cities to create a unique identity, to differentiate themselves from competitors, has become critical. Many places promote spectacular scenery, good quality of life, friendly people, and a sound business infrastructure. However, these factors are no longer differentiators, so places need a strong brand identity to stand out in order to attract people to live, work, and play. But brand development is often driven by short-term top-down approaches with limited community participation, where the primary tool of brand expression becomes the final marketing campaign. This article reports on a qualitative approach to build a place brand from the bottom up, with wide participation from all members of the community. With a methodology based on place brand-building theory, charettes and in-depth interviews were conducted with local stakeholders, resulting in a positioning statement that was used to develop brand communications materials. Based on the research process and results of the case study, the authors present a community-based place brand development model.